Hyperhomocysteinemia may be a resistance factor in tocolytic treatment with ? mimetics - Celik, H; Ayar, A; Tug, N (Elsevier, 2003)
Homocysteine is an intermediate amino acid in the methionine metabolism which does not take place in the structure of proteins. Plasma homocysteine levels can be elevated by a variety of genetic and nutritional factors. Hyperhomocysteinemia is an independent risk factor for cardiovascular diseases and common obstetric problems. Mildly elevated levels of homocysteine have been implicated in a number of disease processes such as atherosclerotic vascular disease and adverse obstetrical outcome. It was shown that the presence of high homocysteine concentrations in the in vitro system had an activating role in myometrial contractions. It is hypothesized that hyperhomocysteinemia in pregnancy is associated with preterm labor in consequence of myometrial contractions. Hyperhomocysteinemia, therefore, could be a treatable cause of this important public health and obstetric concern. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: Preterm Delivery; Homocysteine; Pregnancy; Labor